Enzyme Conditioning of Chicken Collagen and Taguchi Design of Experiments Enhancing the Yield and Quality of Prepared Gelatins - Mokrejš, Pavel; Gál, Robert; Pavlačková, Jana (International journal of molecular sciences, 2023)
During the production of mechanically deboned chicken meat (MDCM), a by-product is created that has no adequate use and is mostly disposed of in rendering plants. Due to the high content of collagen, it is a suitable raw material for the production of gelatin and hydrolysates. The purpose of the paper was to process the MDCM by-product into gelatin by 3-step extraction. An innovative method was used to prepare the starting raw material for gelatin extraction, demineralization in HCl, and conditioning with a proteolytic enzyme. A Taguchi design with two process factors (extraction temperature and extraction time) was used at three levels (42, 46, and 50 °C; 20, 40, and 60 min) to optimize the processing of the MDCM by-product into gelatins. The gel-forming and surface properties of the prepared gelatins were analyzed in detail. Depending on the processing conditions, gelatins are prepared with a gel strength of up to 390 Bloom, a viscosity of 0.9-6.8 mPa·s, a melting point of 29.9-38.4 °C, a gelling point of 14.9-17.6 °C, excellent water- and fat-holding capacity, and good foaming and emulsifying capacity and stability. The advantage of MDCM by-product processing technology is a very high degree of conversion (up to 77%) of the starting collagen raw material to gelatins and the preparation of 3 qualitatively different gelatin fractions suitable for a wide range of food, pharmaceutical, and cosmetic applications. Gelatins prepared from MDCM by-product can expand the offer of gelatins from other than beef and pork tissues.
Keywords: Cattle; kur domácí; Animals; skot; Gelatin; biomaterials; teplota; Chickens; Food; Collagen; zero-waste; collagen; kolagen; by-product; gelatin; mechanically deboned chicken meat; Temperature; enzyme conditioning; želatina; zvířata; potraviny; Taguchi design